The Influence of Parenteral Energy and Protein Intakes in the First Week on the Growth of Very Low Birth Weight Babies - Christopher Geoffrey Alexander Aiken (JCDR Research and Publications Pvt. Ltd., 2013)
Objective: To compare growth of very low birth weight (VLBW) infants given standard total parenteral nutrition (TPN), providing 25kcal/g amino acids, and high calcium TPN, providing 30kcal/g amino acids. Energy to protein ratio affects protein catabolism. Regimens providing less than 30kcal/g amino acids increase protein catabolism, leaving insufficient for growth. Study Design: All VLBW infants given high calcium TPN during the first 44 months of its use were compared with all those given standard TPN over the previous 24 months. Growth was assessed from mineral retention on TPN and anthropometric measurements until discharge from paediatric follow up. Ignoring stools, mineral retention equaled TPN intake minus urine excretion measured from daily urine samples: Mineral excretion mmol/kg/day = Urine mineral/ urine creatinine x creatinine production Creatinine production μmol/kg/day = -2.07 + 2.34 x gestational age in weeks. Results: 16 infants fed standard TPN retained less than 1 mmol/kg/day of calcium and phosphate and developed high alkaline phosphatase. TPN increased their protein catabolism. Their neonatal growth in weight and head circumference was retarded affecting their childhood growth. 23 infants fed high calcium TPN retained minerals at optimal rates and maintained normal alkaline phosphatase. TPN did not increase their protein catabolism, unless they received dexamethasone, which improved their breathing, allowing more TPN that prevented nitrogen retention from falling. Their neonatal growth was normal and did not affect their childhood growth. 6 (26%) infants, all below 29 weeks, needed insulin to control hyperglycaemia while on TPN, with normal glucose control in more mature babies. Conclusion: High calcium TPN with 30kcal/g amino acids produces normal growth. Standard TPN with 25kcal/g amino acids increases protein catabolism compromising growth.